REINTERPRETASI KONSEP ISLAM KAFFAH PERSPEKTIF FAKHRUDDIN AL-RAZI : (Aplikasi Teori Hermeneutika Hans-Georg Gadamer) - Mila Aulia; Moh. Nurun Alan Nurin Perdana Kusuma; Roudlotul Jannah (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2022)
The existence of hermeneutics in turn has a major influence on the development of a multi-interpretative world of interpretation. Hans-Georg Gadamer's theory is used to interpret the Koran through its hermeneutical style of thinking which has a philosophical-productive nuance. Meanwhile, Fakhruddin al-Razi is a popular interpretation scholar who often carries out theological debates among rationalists and traditionalists through his logical ideas. This study departs from the concept of Islam kaffah which is warmly echoed by religious activists as a theological discourse to welcome Muslims to return to